Fatty acid profiles of Trachinus radiatus Cuvier, 1829 (Perciformes‐Trachinoidei, Trachinidae). (6th April 2017) - Đikić, D.; Landeka, I.; Franjević, D.; Skaramuca, D.; Fuchs, R.; Matić Skoko, S.; Tutman, P.; Lukić, I.; Skaramuca, B.
Summary: The goal of this study was to analyse the fatty acid (FA) profiles of the streaked (starry) weever ( Trachinus radiatus ), a prized food fish in the countries of its distribution. Fish ( N = 20) were sampled in July 2011. Location: 42.761019°N, 17.765090°W; Adriatic Sea, Elaphite Islands near Dubrovnik, Croatia, at 5–10 m depth using longline hooks; body length ranges: 24.1–47.2 cm, weight ranges: 120–960 g. Morphological species determination was genetically confirmed (Folmer region of COI gene). Biochemical analysis of T. radiatus muscular tissue (filet) revealed average ± SD dry matter of 252.3 ± 14.8 g/kg w.w.; moisture of 747.7 ± 14.8 g/kg w.w., and ash of 28.0 ± 6.9 g/kg w.w. Intramuscular crude protein content exceeded the total lipid (TL = 11.9 ± 4.0 g/kg w.w.) content approximately 17.7 fold. Unsaturated FA (UFA) was higher than saturated FA (SFA), with a predominance of polyunsaturated FA (PUFA). The ω3:ω6 ratio was 4.9:1, respectively. Among individually determined fatty acids, the PUFA 22:6n3 (DHA) was highly present (29.99 ± 2.75% TL) followed by a relatively high 20:5n3 (EPA) content. There was 25 fold higher EPA content than of substrate αLNA, and a 15.5 fold higher DHA content to DPAn3. Such ratios indicate that besides trophic ingestion, FA bioconversion elongase/desaturase synthesis pathways toward ω3 PUFA in Weevers could be highly efficient.